Ruptured Gastroduodenal Artery Pseudoaneurysms as a Complication of Pancreatitis - Haider Ghazanfar; Abhilasha Jyala; Sameer Datta Kandhi; Dongmin Shin; Kazi Samsuddoha; Harish Patel (Case Reports in Gastroenterology, 2023)
Visceral artery pseudoaneurysms is a known vascular complication of pancreatitis that can lead to life-threatening hemorrhages with a high mortality rate if left untreated. We present a case of ruptured gastroduodenal artery pseudoaneurysm in a 68-year-old male with acute pancreatitis presenting with fatal gastrointestinal and retroperitoneal bleeding that was successfully managed with endovascular coil embolization of the involved vasculature. Patients with hemorrhagic pancreatitis or those presenting with unexplained retroperitoneal or gastrointestinal bleeding in the setting of pancreatitis with an unexplained drop in hematocrit or sudden expansion of pancreatic fluid collection should be screened in a timely manner for pseudoaneurysm using CT angiogram of the abdomen, which is the gold standard imaging modality to identify pseudoaneurysms. Once pseudoaneurysm is diagnosed, it should be treated immediately. Endovascular treatment options are now favored over surgical options in most cases.